The Effectiveness of Applying Teaching Skills of Teachers on Students' Learning Motivation - Mufidah, Mufidah; Hidayat, Taufik; Kaharu, Sarintan N.; Nuraini, Nuraini; Akina, Akina (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Critical thinking is necessary to search for new ideas and discoveries to address the complexities of life in the 21st century. One effort to meet this need is the implementation of a team-based project-based learning model. This model aims to influence students' critical thinking skills. However, the implementation of this learning approach is not yet supported by well-developed instructional materials. The existing modules still have some limitations as they were created at the beginning of the program implementation, and certain field conditions require adjustments and improvements to align with the encountered problem contexts. This research follows the Research and Development approach, using the development steps proposed by Borg and Gall, which include: 1) Needs analysis; 2) Planning instructional material development; 3) Design validation; 4) Small group product testing; 5) Product revision; and 6) Large group product testing. The data sources for this study consist of: (1) Expert assessment data, (2) Small group testing results, and (3) Large group testing results. The research was conducted in the Elementary School Teacher Education Program at Tadulako University, with the subjects being students from the 2019/2020 cohort. The results of the study indicate that the Team-Based Project-based Learning Module for Elementary School Number Operations is considered valid and practical based on the validation results from subject matter experts, media experts, initial field testing, and main field testing. Therefore, the module is deemed suitable for use.